1976
DOI: 10.1139/m76-114
|View full text |Cite
|
Sign up to set email alerts
|

Some properties of an unidentified halophile: growth characteristics, internal salt concentration, and morphology

Abstract: An unidentified halophile isolated from plates of a complex agar medium containing 4.25 M NaCl showed optimum growth in broths containing 0.5-1.0 M NaCl but exhibited a wide range of growth from 0.045-4.5 M. The organism can be classified as a facultative halophile with wide salt tolerance. Logarithmic phase cells grown in media containing 0.5 M NaCl were rod-shaped in long chains which changed to smaller, single, or paired cells in stationary growth. The internal Na+ and K+ concentrations were 0.05 M and 0.34… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
31
0

Year Published

1978
1978
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(37 citation statements)
references
References 3 publications
6
31
0
Order By: Relevance
“…aFor the first two-thirds of the protein for which the sequence has been determined increase in the cw-helicity from 35--56% as the salt concentration is increased from 0.1-3.0 M. The addition of trifluoroethanol again promotes almost total helicity in the molecule. The estimate of 56% o-helix approaches that of E. coli, and the results are consistent with a protein structure adapted to a somewhat higher internal salt concentration than E. coli [2] .…”
Section: Resultssupporting
confidence: 79%
“…aFor the first two-thirds of the protein for which the sequence has been determined increase in the cw-helicity from 35--56% as the salt concentration is increased from 0.1-3.0 M. The addition of trifluoroethanol again promotes almost total helicity in the molecule. The estimate of 56% o-helix approaches that of E. coli, and the results are consistent with a protein structure adapted to a somewhat higher internal salt concentration than E. coli [2] .…”
Section: Resultssupporting
confidence: 79%
“…For Halobacterium halobium values of 2-5-2.75 p1 (mg protein)-' (Bakker et al, 1976;Michel & Oesterhelt, 1980), and for Vibrio alginolyticus values of 3.3 p1 (mg protein)-' (Tokuda & Unemoto, 1982) were recorded. In an unidentified moderately halophilic bacterium the space inaccessible to inulin decreased in the stationary phase and also with increasing salt concentrations (Matheson et al, 1976). These authors gave values of the space inaccessible to inulin of 4-94 p1 (mg protein)-for exponentially growing cells, whereas for stationary-phase cultures the value was 2-56 pl (mg protein)-', when grown at low sodium concentrations (about 0.6 M-sodium).…”
Section: Discussionmentioning
confidence: 98%
“…Strain NRCC 41227 T was reported as a medium contaminant by Matheson et al (1976) and served as a model for some physiological studies (Falkenberg et al, 1976 ;Ken-Dror et al, 1984). A summary of these studies conducted on the two strains can be found in a recent review (Ventosa et al, 1998) about moderately halophilic bacteria, which are defined as those micro-organisms able to grow optimally in media containing 3-15 % (w\v) NaCl (Kushner & Kamekura, 1988).…”
Section: Introductionmentioning
confidence: 99%